7x-6y=-1

5x-4y=1

7x-6y=-1

5x-4y=1

Tutors, please sign in to answer this question.

I am going to use elimination method to solve.

14x - 12y = -2 First equation multiplied by 2

-15x +12y = -3 Second equation multiplied by -3

-x = -5

x = 5 Multiply each side by -1

7x - 6y = -1 Equation 1

7(5) - 6y = -1 Substitute the value of x that you found into equation 1

35 - 6y = -1 Simplify

-6y = -1 - 35 Subtract 35 from each side

-6y = -36 Simplify

y = 6 Divide each side by -6

Amaan M.

Math/Economics Teacher

New York, NY

5.0
(68 ratings)

Cassandra K.

Creative and Engaging Math and English Tutor

New York, NY

5.0
(294 ratings)

Wesley L.

Premier MIT Math Tutor and SHSAT/SAT/ACT Specialist

New York, NY

5.0
(228 ratings)